2015
DOI: 10.1186/s12885-015-1516-2
|View full text |Cite|
|
Sign up to set email alerts
|

Spectrum and frequencies of BRCA1/2 mutations in Bulgarian high risk breast cancer patients

Abstract: BackgroundAbout 3885 women are diagnosed with breast cancer and 1285 die from the disease each year in Bulgaria. However no genetic testing to identify the mutations in high-risk families has been provided so far.MethodsWe evaluated 200 Bulgarian women with primary invasive breast cancer and with personal/ family history of breast cancer for the presence of unequivocally damaging germline mutations in BRCA1/2 using Sanger sequencing.ResultsOf the 200 patients, 39 (19.5 %) carried a disease predisposing mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
2
14
1
Order By: Relevance
“…The age characteristic of patients who have breast cancer in the present study, revealed that the highest frequency of breast cancer patients among (40-50) years old (40%), followed by the age group of ( 30-39) years old (20%) , and the less frequency in the age (19-29) years (10%) , which has no signi icant differences as compared with control group (p > 0.05) mean 46.38 years (SD14.34) , so breast cancer is a disease of all ages, considering the entire lifespan (Walters, 2004). The results of our present study are agreed with (Walters, 2004) since the results of their study which included 200 Bulgarian females with breast cancer (postoperative and the age ranged from 25 to74 years) selected by the established genetic testing criteria, the mean age of the patients at diagnosis was 49.5 years , and no signi icant association between patients group and controls group (p > 0.05) (Dodova and Ivanova, 2015). So our indings are comparable with a study conducted an average 12% of women worldwide related breast cancer, their ages ranged between <40 ->70 years and showed 48.5 years mean of patients ages (Mcguire, 2015).…”
Section: -Demographic Characteristicssupporting
confidence: 92%
“…The age characteristic of patients who have breast cancer in the present study, revealed that the highest frequency of breast cancer patients among (40-50) years old (40%), followed by the age group of ( 30-39) years old (20%) , and the less frequency in the age (19-29) years (10%) , which has no signi icant differences as compared with control group (p > 0.05) mean 46.38 years (SD14.34) , so breast cancer is a disease of all ages, considering the entire lifespan (Walters, 2004). The results of our present study are agreed with (Walters, 2004) since the results of their study which included 200 Bulgarian females with breast cancer (postoperative and the age ranged from 25 to74 years) selected by the established genetic testing criteria, the mean age of the patients at diagnosis was 49.5 years , and no signi icant association between patients group and controls group (p > 0.05) (Dodova and Ivanova, 2015). So our indings are comparable with a study conducted an average 12% of women worldwide related breast cancer, their ages ranged between <40 ->70 years and showed 48.5 years mean of patients ages (Mcguire, 2015).…”
Section: -Demographic Characteristicssupporting
confidence: 92%
“…The amount of rare mutations found in our study may be similar in other countries assumed to have a strong founder effect. In a recent study from Bulgaria, 200 individuals from breast/ovarian cancer families were genotyped with sequencing, and comparable results were found [ 24 ]. Two new, and five previously known mutations were identified in BRCA2 , while two new and six previously known mutations were identified in BRCA1 .…”
Section: Discussionmentioning
confidence: 73%
“…However, controversial reports exist about the role of SNPs in these BRCA1/2 genes for the induction of human breast and ovarian cancer (HBOC). 2 , 18 , 21 , 22 , 23 Dombernowsky et al 22 reported that missense mutations cannot explain the risk of HBOC in women with familial history. Contrarily, Dodova et al 21 in their study implicated the role of missense variants which may be deleterious.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 18 , 21 , 22 , 23 Dombernowsky et al 22 reported that missense mutations cannot explain the risk of HBOC in women with familial history. Contrarily, Dodova et al 21 in their study implicated the role of missense variants which may be deleterious. In an Iranian population, Neamatzadeh et al 23 detected these polymorphic SNPs at higher frequency in BRCA1 and BRCA2 genes compared to control subjects supporting our data.…”
Section: Discussionmentioning
confidence: 99%